Big Data Empowered Logistics Services Platform - Naoufel Cheikhrouhou; Paul de Vrieze; Emanuele Giovannetti; Shaofeng Liu; Ying Xie; Lai Xu; Hongnian Yu (International Telecommunications Society (ITS), 2016)
Logistics section is one of the most important industrial sections to contribute to European economy. To improving efficiency and energy efficient of logistics, European Commission call new research theme `smart, green and integrated transport' in its H2020 program. The paper presents a version on providing a cloud based platform for supporting big data empowered logistics services to respond this call. The research is supported by inter-disciplinary approaches, which brings experts from telecommunication, cloud computing, sensor networking, service-oriented computing, data analysis, transportation, and logistics areas to work together to provide real-world solutions for future logistics. The research questions and challenges of the platform are highlighted. Overall architecture and data collection are presented.
Keywords: 330